EFFICACY OF POST-EMERGENCE HERBICIDES ON WEED CONTROL, PRODUCTIVITY AND ECONOMICS OF SUGARCANE - U , VIJAYA BHASKAR REDDY (The Journal of Research ANGRAU, 2026)
A field experiment in sugarcane weed control was conducted from 2020-21 to 2022-23 in randomized block design with three replications in alluvial soils of Krishna – Godavari delta of Andhra Pradesh. Results revealed that, comparatively higher weed control efficiency was recorded with post-emergence application of tembotrione @ 125 g/ha + halosulfuran methyl @ 125 g/ha fb IC at 60 and 90 DAP. Significantly more cane yield was recorded with application of topramezone @ 40 g/ha + halosulfuron methyl @ 125 g/ha fb IC at 60 and 90 DAP (115.9 t/ha) which was however statistically at par with rest of the herbicide treatments. The quality parameters like sucrose %, CCS and purity % were not affected by the herbicide treatments. With regard to economics, higher gross returns (Rs. 3,43,296), net returns (Rs. 45,130/-) and B:C ratio (1.15) was recorded with topramezone @ 40 g/ha + halosulfuron methyl @ 125 g/ha fb IC at 60 and 90 DAP